The Influence Of Brand Trust On Brand Loyalty With Brand Love As Mediator (Case Study Of Kopi Roemah Kesambi) - Auliya Safitri; May Dedu; Soesanty Maulany (International Journal of Business, Economics, and Social Development, 2026)
Coffee consumption in Indonesia has changed from being a necessity to a part of a modern lifestyle due to the industry's rapid growth. This is especially true for the younger generation, whose visits to coffee shops are influenced not only by the taste but also by the atmosphere, brand image, and emotional attachment provided. This phenomenon provides a dilemma for local coffee shops such as Kopi Roemah Kesambi which, despite having excellent sales levels, nevertheless confronts variations in client retention such that brand loyalty has not been securely established. Although contemporary marketing theory highlights the significance of consumer emotional attachment to the brand as a foundation for long-term loyalty, the role of brand trust and brand love in forming brand loyalty in the context of local coffee shops is still rarely studied. This creates a research gap because the majority of prior studies emphasize product customer quality and satisfaction as determinants of loyalty. With a population of 368 active Kopi Roemah Kesambi customers and a sample of 192 respondents chosen using the Slovin formula with a 5% margin of error, this study employs a quantitative approach with an explanatory research method and a probability sampling technique through simple random sampling to close this gap. Data were obtained by a closed questionnaire based on a 1-5 Likert scale and analyzed using SEM-PLS through SmartPLS 4.0. It is hoped that this study will add to the body of knowledge on consumer behavior and help local coffee shops create more sustainable and successful customer retention strategies by examining the impact of brand trust on brand loyalty, with brand love serving as a mediator.